2004
DOI: 10.1063/1.1649553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heat Pipe Working Fluids In The Temperature Range 450 to 700 K

Abstract: In the temperature range of 450-700 K, there are currently no working fluids that have been validated for heat pipes and loop heat pipes, with the exception of water in the lower portion of the range. This paper reviews a number of potential working fluid including several organic fluids, mercury, sulfur/iodine, and halides. Physical property data are used where available, and estimated where unavailable using standard methods. The halide salts appear to possess attractive properties, with good liquid transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…A survey of working fluids in the temperature range from 450 to 700 K found that water was the best working fluid for temperatures below 550 K, with a merit number roughly ten times higher than other intermediate temperature working fluids (Anderson et al, 2004).…”
Section: Titaniumavater Compatibilitymentioning
confidence: 99%
“…A survey of working fluids in the temperature range from 450 to 700 K found that water was the best working fluid for temperatures below 550 K, with a merit number roughly ten times higher than other intermediate temperature working fluids (Anderson et al, 2004).…”
Section: Titaniumavater Compatibilitymentioning
confidence: 99%
“…The vast majority of commercial heat pipe based technologies are limited to temperatures below 230 • C. Water, ammonia, or refrigerants are mainly used as working fluids in this range [4]. The technology is mature with an excellent track record with regard to performance and reliability, and thermosyphons are commercially available at reasonable cost [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between the two is excellent for the three fluids where both surface tension and critical properties are known. Anderson et al (2004) discussed the evaluation of the organic fluids, aniline, naphthalene, toluene, hydrazine, and phenol. In general, the vapor pressures as well as the merit numbers of the organic fluids are lower than those of water at a given temperature.…”
Section: Surface Tension Estimationmentioning
confidence: 99%